2013
DOI: 10.1093/infdis/jit466
|View full text |Cite
|
Sign up to set email alerts
|

Dependence of Efavirenz- and Rifampicin-Isoniazid–Based Antituberculosis Treatment Drug-Drug Interaction on CYP2B6 and NAT2 Genetic Polymorphisms: ANRS 12154 Study in Cambodia

Abstract: We investigated the population pharmacokinetics and pharmacogenetics of efavirenz in 307 patients coinfected with human immunodeficiency virus and tuberculosis and included in the Cambodian Early vs Late Initiation of Antiretrovirals trial (CAMELIA) in Cambodia. Efavirenz (600 mg/d) and stavudine plus lamivudine were administered in addition to standard antituberculosis treatment, including rifampicin and isoniazid. Blood samples were obtained a mean of 14 hours after efavirenz intake at weeks 2 and 6 after in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
37
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 48 publications
8
37
0
Order By: Relevance
“…Our results are supported by a recent pharmacogenetic study of treated coinfected Cambodian patients, among whom CYP2B6 516TT patients who also carried slow-metabolizer N-acetyltransferase 2 (NAT2) genotypes showed even higher efavirenz levels than those without these NAT2 variants (22). N-Acetylation by NAT2 is the main mechanism for clearance of isoniazid, and although plasma concentrations of isoniazid were not measured, it was speculated that patients with slow-metabolizer NAT2 genotypes had increased isoniazid concentrations with resultant increased inhibition of efavirenz clearance.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Our results are supported by a recent pharmacogenetic study of treated coinfected Cambodian patients, among whom CYP2B6 516TT patients who also carried slow-metabolizer N-acetyltransferase 2 (NAT2) genotypes showed even higher efavirenz levels than those without these NAT2 variants (22). N-Acetylation by NAT2 is the main mechanism for clearance of isoniazid, and although plasma concentrations of isoniazid were not measured, it was speculated that patients with slow-metabolizer NAT2 genotypes had increased isoniazid concentrations with resultant increased inhibition of efavirenz clearance.…”
Section: Discussionsupporting
confidence: 83%
“…In a cross-sectional study of 56 adult Ghanaian patients, we showed that efavirenz concentrations were significantly higher in homozygous CYP2B6 c.516TT patients receiving antituberculosis therapy than in those not receiving this therapy, while there was no effect of the antituberculosis drugs in patients with the c.516GG or c.516GT genotypes (6). This result was subsequently confirmed in two different longitudinal studies, including a study of 32 coinfected South African children (21) and a study of 307 coinfected Cambodian adults (22) that measured efavirenz concentrations during and following discontinuation of antituberculosis therapy. In both studies, efavirenz concentrations were significantly higher during the initial antituberculosis treatment phase in patients with CYP2B6 slow-metabolizer genotypes (primarily c.516TT), but there was no difference in CYP2B6 intermediate or fast-metabolizer patients.…”
supporting
confidence: 55%
See 1 more Smart Citation
“…For example, rifampin reduces concentrations of the newest TB drug, bedaquiline, by 50% (29). Conversely, isoniazid can inhibit metabolizing enzymes, and unexpected effects may occur when rifampin and isoniazid are coadministered with a third drug (30,31). Second, rifamycin antibiotics like rifampin and rifapentine have dose-dependent treatment-shortening potential, but evaluating high-dose rifamycins is challenging because the magnitude of drug interactions at increased rifamycin doses is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…In a multivariate regression analysis of 62 patients from Rwanda being treated for HIV and TB infection, CYP2B6 c.516G>T, CYP2B6 c.983T>C, and CYP2A6 c.1093G>A contributed 43%, 29%, and 27% of the total variance in EFV plasma levels, respectively [50]. Another study took into account the NAT2 genotype, and found that patients with the CYP2B6 c.516G>T genotype TT and a NAT2 slow acetylator genotype (two “slow” alleles NAT2 * 5 , * 6 or * 7 determined by genotyping rs1801280, rs1801279, rs1799930 and rs1799931) had the lowest apparent EFV clearance when treated concomitantly with anti-TB drugs [62]. On the other hand, patients with the CYP2B6 c.516G>T genotype GG with the NAT2 rapid acetylator genotype had the highest levels of clearance [62].…”
Section: Pharmacogeneticsmentioning
confidence: 99%